Bioameliorant: Soil Amelioration and Nutrient Distribution in Organosol Soil Through the Application of Macro and Micro Fertilizer to Optimizing on the Growth of Rubber Trees (Hevea brasiliensis Muell. Arg.) - Rhiki Budianto; Erwin Junaidi Lubis (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Soil Ameliorants are materials used to improve soil, playing a key role in rehabilitating and enhancing the physical, chemical and biological properties of the soil. In the Organosol soil under study—commonly referred to as Histosol or Peat soil—the soil-improving materials play a vital role, as this soil is highly acidic, has very low levels of macro- and micro-nutrients, and contains organic acids that can be toxic to plants. The distribution of nutrients studied in Organosol soil shows a concentration of organic matter in the upper layer of the Organosol, where abundant nitrogen is bound organically; however, phosphorus, potassium, calcium and magnesium are very low due to leaching processes. In this study, the application of organic matter that supports microbial activity in Organosol soil—specifically the application of oil palm frond ash—can increase potassium (K) levels and soil acidity (pH), whilst the application of soil ameliorants can improve nutrient deficiencies in phosphorus (P), potassium (K), calcium (Ca), and magnesium (Mg), demonstrating a significant and pronounced effect when applied to Organosol soil.